Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-462
|View full text |Cite
|
Sign up to set email alerts
|

Separated-Flow Transition: Part 2 — Experimental Results

Abstract: The present paper focuses on presenting the results of the experimental investigation of the transition process in separated boundary layers on a flat plate at zero incidence, with imposed adverse pressure gradients. The combined effects of Reynolds number and adverse pressure gradient strength on the transition mechanism, bubble geometry, and bubble bursting process are studied. The flow structures and the unsteady aspects associated with separated-flow transition are analyzed for three representative experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…According to Hatman and Wang (20) , this is a typical laminar separationshort bubble transition mode, dominated by the Kelvin-Helmholtz (K-H) instability. Hatman and Wang (16) found the maximum value of the rms velocity for this transition mode was approximately 0.18, which is similar to the present compressible NLES results of approximately 0.17, found in the region around the reattachment point x/C = 0.98.…”
Section: Mean and Rms Fieldssupporting
confidence: 89%
See 3 more Smart Citations
“…According to Hatman and Wang (20) , this is a typical laminar separationshort bubble transition mode, dominated by the Kelvin-Helmholtz (K-H) instability. Hatman and Wang (16) found the maximum value of the rms velocity for this transition mode was approximately 0.18, which is similar to the present compressible NLES results of approximately 0.17, found in the region around the reattachment point x/C = 0.98.…”
Section: Mean and Rms Fieldssupporting
confidence: 89%
“…A typical value of H at separation in a laminar boundary layer is approximately 3.5 (20) . As Hatman and Wang (16) reported, H reaches a maximum value in the region around the maximum displacement of the separated shear layer x MD . From Fig.…”
Section: Mean and Rms Fieldsmentioning
confidence: 74%
See 2 more Smart Citations
“…He also tried to identify critical parameters for the bursting onset and showed that for the longer bubbles and low freestream turbulence, much of the flow within the bubble is laminar and Tollmien-Schlichting instabilities have been observed. The phenomenon of transition triggered by separation bubble was also described by Hatman and Wang [5] [6][7] [8]. For constant freestream conditions (turbulence intensity and adverse pressure gradient) when lowering the Reynolds number the bubble size increases.…”
Section: Introductionmentioning
confidence: 95%